The regulatory roles of aquaporins in the digestive system - Shengtao Liao; Li Gan; Lin Lv; Zhechuan Mei (Genes and Diseases, 2021)
Aquaporins (AQPs) are highly conserved small transmembrane proteins, which are responsible for the water transport across the cell membrane. AQPs are abundantly expressed in numerous types of cells such as epithelial and endothelial cells. The expression of AQP-1, -3, -4, -5, -8 and -9 were found in the digestive system, where these six AQP isoforms serve essential roles including mediating the transmembrane water transport and regulating the secretion of gastrointestinal (GI) fluids, consequently facilitating the digestion and absorption of GI contents. In addition, the expression levels of AQPs are controlled by various factors, and AQPs can stimulate numerous signaling pathways; however, aberrant expression of AQPs in the GI tracts are associated with the initiation and development of numerous diseases. Thus, this review provides an overview of the expression and functions of AQPs in the digestive system.